PENGARUH INDEPENDENSI, PENGALAMAN KERJA, DAN PROFESIONALISME AUDITOR INSPEKTORAT TERHADAP KUALITAS AUDIT INTERNAL DENGAN ROLE CONFLICT SEBAGAI VARIABEL PEMODERASI: STUDI KASUS DI KANTOR INSPEKTORAT KABUPATEN LOMBOK TENGAH - Arifin, Arifin (Penerbit Lafadz Jaya, 2026)
This study aims to examine the influence of inspectorate auditor independence, work experience, and professionalism on internal audit quality, with role conflict as a moderating variable. This study attempts to address the conflict within the government bureaucracy related to audit quality. The subjects of this study were inspectorate auditors working at the Central Lombok Regency Inspectorate. The sampling technique used convenience sampling by distributing questionnaires. The data analysis method used was moderated regression analysis (interaction test). The results of this study indicate that inspectorate auditor professionalism has a positive effect on audit quality. Meanwhile, inspectorate auditor independence and work experience do not. Furthermore, role conflict weakens the effect of auditor professionalism on audit quality. Role conflict does not weaken the effect of independence and work experience on audit quality.